Ectoparasitic load of Blue-crowned Parakeet (Aratinga a. acuticaudata Psittacidae) nestlings - Aramburu, Rosana Mariel (2013)
The Blue-crowned Parakeet (Aratinga a. acuticaudata) ranges through Brazil, Bolivia, Paraguay, Uruguay, and Argentina, where it nests in cavities of mature trees. Our objective was identify the arthropods parasitizing the nestlings in a population of Chaco and determine their prevalence, intensity and abundance. In 2006 and 2007, we studied 24 nestlings from ten nests in the Reserva Provincial Loro Hablador. We exposed nestlings to ethyl acetate vapors and then removed parasites by agitating feathers. Also, some tree holes with nests were visually prospected. In the laboratory, we identified the chewing lice Paragoniocotes anomalus (Phthiraptera: Philopteridae), Heteromenopon laticapitis, and Psittacobrossus cf. anduzei (Phthiraptera: Menopodidae), the mite Ornithonyssus bursa, the hematophagous bugs Triatoma sordida and Ornithocoris toledoi, and botfly Philornis sp. This is the first record of T. sordida, O. bursa, and P. cf. anduzei parasitizing Blue-crowned Parakeet in Argentina, and the first record of Philornis sp. parasitizing parrots in Argentina. Ornithonyssus bursa was the most prevalent (90%), H. laticapitis had the highest mean abundance (7 lice/parrot), and O. toledoi the highest intensity parasite (32.5 bugs/parrot). Haematophagous species appeared at younger host ages (25 days) than penniphagous (35 days). Further studies are needed to evaluate the impact of these species on the nestling development and breeding success in the Blue-crowned Parakeet.